Microscopic models of hardness - Gao, F.M.; Gao, L.H. (Сверхтвердые материалы, 2010)
Recent developments in the field of microscopic hardness models have been reviewed. In these models, the theoretical hardness is described as a function of the bond density and bond strength. The bond strength may be characterized by energy gap, reference potential, electron-holding energy or Gibbs free energy, and different expressions of bond strength may lead to different hardness models. In particular, the hardness model based on the chemical bond theory of complex crystals has been introduced in detail. The examples of the hardness calculations of typical crystals, such as spinel Si₃N₄, stishovite SiO₂, B₁₂O₂, ReB₂, OsB₂, RuB₂, and PtN₂, are presented. These microscopic models of hardness would play an important role in search for new hard materials.